Leadership and Knowledge Management in SMEs: Organizational Culture as Moderation - Rumijati, Aniek; Arifiani, Ratya Shafira; Hakim, Arif Rahman (Universitas Proklamasi 45, 2024)
Knowledge management is important for small and medium-sized businesses to maintain their competitive position and drive innovation. The main obstacles that hinder the spread of knowledge management practices in SMEs include cultural aspects, leadership, and limited managerial capacity related to technology and knowledge gaps. Therefore, this study analyzed the effect of transformational and transactional leadership on knowledge management in SMEs and the moderating of organizational culture. This research was collected using a questionnaire. The sample of this study was leaders of Small and Medium Industries in Mojowarno District, Jombang, East Java, Indonesia with 62 respondents. The analytical method used a moderation test using the SmartPLS 3 program. The results of the study revealed that transformational leadership had a significant effect on knowledge management while transactional leadership did not have a significant impact on knowledge management; team culture strengthened the influence of transformational and transactional leadership on knowledge management, and there was no moderating role of adhocracy culture and market culture. These findings show that transformational leadership plays a major role in the application of knowledge management in SMEs. However, transformational and transactional leadership collaboration has a major impact on the successful implementation of knowledge management. Clan culture contributes greatly to strengthening the leadership role of knowledge management.